EFFORTS TO IMPLEMENT THE PRINCIPLE OF COORDINATION BETWEEN POLICE INVESTIGATORS AND PROSECUTORS IN PROCESSING CRIMINAL CASES IN THE JURISDICTION OF THE PEKANBARU POLICE STATION - Aristyan , Christ; Harahap, Emirza Henderlan (PT. Altin Riset Publishing, 2024)
To enforce criminal law, there needs to be coordination between police investigators and public prosecutors. This is to the existing provisions in the Criminal Procedure Code in the form of criminal offenses must be disclosed, investigators must notify the public prosecutor if there is a termination or extension in the case. If the functional relationship and coordination do not go well, there will be many arrears of problems in the Prosecutor's Office, thus affecting the problem-solving process. Likewise, on the other hand, if there is coordination and communication between investigators and public prosecutors, they will be able to resolve each case properly. So, the obstacles in the implementation of the principle of coordination between police investigators and public prosecutors are the lack of communication, prioritizing the interests of their departments, the existence of sectoral arrogance, and lack of trust in the police to enforce the law and so on. This also grows from the stigma of the community towards the police so that it causes difficulties in conveying aspirations in the field, neglect of legal aspects, police ethics whose morale is still low, and equipment and investigations are still limited.